2008
DOI: 10.1111/j.1438-8677.2008.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell death upon H2O2 induction in the unicellular green alga Micrasterias

Abstract: In the present study we investigate whether the unicellular green alga Micrasterias denticulata is capable of executing programmed cell death (PCD) upon experimental induction and by which morphological, molecular and physiological hallmarks it is characterized. This is particularly interesting as unicellular fresh water green algae growing in shallow bog ponds are exposed to extreme environmental conditions and the capability to perform PCD may provide an important strategy to guarantee survival of the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 86 publications
(105 reference statements)
5
46
0
Order By: Relevance
“…After coculturing with M. spicatum, it was observed that external configuration of M. aeruginosa cells remained intact while the interior structures changed, in which inclusions collapsed, DNA dispersed, and the nuclear zone boundary became less distinct or even disappeared. Similar ultrastructure alterations were previously reported for M. aeruginosa exposed to the alleochemical gramine (0.5-8.0 mg L −1 ) (Hong et al 2010), M. denticulata treated with H 2 O 2 (Darehshouri et al 2008), and D. tertiolecta deprived with light (Segovia et al 2003). In this study, these morphological changes, DNA fragmentation, and activation of caspase-3-like activity detected are in accordance with PCD hallmarks observed under adverse conditions by others (Moharikar et al 2006;Berman-Frank et al 2004;Zuppini et al 2007).…”
Section: Discussionsupporting
confidence: 88%
“…After coculturing with M. spicatum, it was observed that external configuration of M. aeruginosa cells remained intact while the interior structures changed, in which inclusions collapsed, DNA dispersed, and the nuclear zone boundary became less distinct or even disappeared. Similar ultrastructure alterations were previously reported for M. aeruginosa exposed to the alleochemical gramine (0.5-8.0 mg L −1 ) (Hong et al 2010), M. denticulata treated with H 2 O 2 (Darehshouri et al 2008), and D. tertiolecta deprived with light (Segovia et al 2003). In this study, these morphological changes, DNA fragmentation, and activation of caspase-3-like activity detected are in accordance with PCD hallmarks observed under adverse conditions by others (Moharikar et al 2006;Berman-Frank et al 2004;Zuppini et al 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Because the type of cell death in microalgae can be species-specific and influenced by a triggering factor, it is challenging to identify a F o r P e e r R e v i e w 15 process common to diverse species of microalgae (Segovia 2008;Jiménez et al, 2009;Affenzeller et al, 2009). In cells of the green alga Micraterias denticulate, the occurrence of PCD, associated with an increase in caspase-like activity, has been observed when cells were exposed to H 2 O 2 (Darehshouri et al, 2008) while a caspase-like independent PCD was reported for the same species upon exposure to salt stress (Affenzeller et al, 2009). Similarly, Jiménez et al (2009) reported the occurrence of a variety of cell death events in the chlorophyte Dunaliella viridis depending on the type of environmental stressors tested.…”
Section: Discussionmentioning
confidence: 99%
“…Although caspases have never been identified in microalgae, antibodies raised against human caspases have been shown to crossreact with extracts of, among others, marine cyanobacteria and chlorophytes (Segovia et al, 2003;Berman-Frank et al, 2004;Moharikar et al, 2006;Zuppini et al, 2007). Additionally, caspase activity assays performed using artificial substrates (designed to be specific for mammalian caspases) showed increases in caspase-like protein activities associated with the occurrence of death in a variety of microalgal species under stress conditions (Berman-Frank et al, 2004;Segovia and Berges, 2005;Ross et al, 2006;Zuppini et al, 2007;Bidle and Bender, 2008;Darehshouri et al, 2008;Affenzeller et al, 2009;Bouchard and Yamasaki, 2009;Jiménez et al, 2009). Finally, the use of mammalian caspase inhibitors has been shown to prevent the occurrence of death in diatoms, dinoflagellates and chlorophytes (Vardi et al, 1999;Bidle and Bender, 2008;Segovia and Berges, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…PCD can be triggered by stress responses such as the presence of ROS (Darehshouri et al 2008), chemical additives (Zuo et al 2011) and temperature fluctuation (Durand et al 2011), factors all involved in cryopreservation. The fact that cell recovery was still observed after samples were subjected to chemical treatment (DMSO and MeOH) and temperature fluctuation (cryopreservation and thawing) suggests that ROS may have a larger role in cell death during the recovery phase.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few circumstances have been identified which stimulate PCD in algae, including but not limited to increased ROS production induced by exogenous hydrogen peroxide (Darehshouri et al, 2008) and acetic acid (Zuo et al, 2011), temperature fluctuation (Durand et al, 2011) and salinity (Shabala, 2009). In this paper, we demonstrate the induction of PCD in the alga Chlorella sorokiniana when grown with glucose as the sole carbon source.…”
Section: Introductionmentioning
confidence: 99%